A High Performance and Platform Independent Web-Based Distance Learning Environment - Yem, Poh Cheang (2001)
The growth of the Internet and the World Wide Web (WWW) has significantly increased the amount of online information and services available to the general population of society. The fast development of high-powered communication technology, together with an increasingly computer-wise society have created new opportunities for the delivery of educational material and distance education on the Web. Among the popular Web-based distance learning systems are WebCT, Blackboard, Lotus LearningSpace and Virtual-U. However, these systems have limitations such as platfonn dependent, slow performance and expensive cost. In this thesis, a Web-based distance learning environment (WebEd 2000) has been developed using Java servlets and random access file to address these problems. It is essentially an extension of WebEd, a first working prototype of Web-based distance learning system developed at the Broadband and ATM Research Group, Universiti Putra Malaysia (UPM). This new version provides significant improvement over its predecessor in various aspects, such as system performance, usability, scalability, security, reliability and stability. WebEd 2000 enables delivering conventional lecture notes over the Web and providing various tools to help in managing and maintaining course materials in a server. It also enables traditional face-to-face interaction to be carried out asynchronously via email and announcement services. Moreover, the system also supports monitoring and tracking of students activities as well as managing of students within a course. WebEd 2000 is mainly developed using the combination of Java servlets and JavaScript technologies. The server-side servlets, together with the binary format random access file, are used to process various client requests and store data, while the client-side JavaScript is used to enable DHTML features and perform less security concern processes such as generating an input dialogue box, hence lessening the workload of the server in relative. Finally, WebEd 2000 can easily be set up and deployed in any platforms with minimal modifications. Flexibility is achieved by utilizing Java technology for the system applications and random access file for the system data repository. It is this platform neutrality of Java bytecodes and binary file format that makes WebEd 2000 a completely platform independent Web-based distance learning environment.